Concomitant Double Ion and Electron Populations in the Earth's Magnetopause Boundary Layers From Double Reconnection With Lobe and Closed Field Lines. Issue 7 (13th July 2018) - Lavraud, Benoit; Jacquey, Christian; Achilli, Timothée; Fuselier, Stephen A.; Grigorenko, Elena; Phan, Tai D.; Øieroset, Marit; McFadden, James; Angelopoulos, Vassilis
Abstract: While double ion populations, with a cold population originating from the solar wind and a hotter one from the magnetosphere, are frequently observed in the low‐latitude boundary layers at the Earth's magnetopause, similar double electron populations are observed less often. A preliminary study of magnetopause crossings characteristics was used to determine the typical locations and energy spectra of ion and electron populations near the magnetopause. Then, we set up an automated detection algorithm for identifying regions with concomitant double populations in both ion and electron energy spectra. The statistical study was carried out on 7 years of Time History of Events and Macroscale Interactions during Substorms particle data, to determine the interplanetary magnetic field conditions in the upstream solar wind for these double populations. The results suggest that such concomitant ion and electron double population boundary layers form preferentially in the subsolar region and under northward interplanetary magnetic field but with a significant BY component. We interpret this finding as the result of reconnection of the same magnetosheath field line in both hemispheres with at least one end reconnecting in its hemisphere at lower latitude with a closed magnetospheric field line that already contains a hot electron source. Key Points: Frequent observation of concomitant double electron and ion population in Earth's boundary layers Statistical analyses show that double populations in both ions and electrons occur mainly at dayside during northward IMF with a large By Result of reconnection between a magnetosheath field line and a magnetospheric field lines already containing hot electrons